PARADIGMA TEORI ARENA PRODUKSI KULTURAL SASTRA: KAJIAN TERHADAP PEMIKIRAN PIERRE BOURDIEU - Kukuh Yudha Karnanta (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2013)
This article discusses the concepts of Pierre Bourdieu’s ideas that integrate literary study, sociology, economics and politics in the study of recent literature. Although Bourdieu’s thought began widely introduced into the social -humanities studies in Indonesia, but the application of these ideas in literary studies in Indonesia are relatively not much done. With Thomas Kuhn’s concept of paradigm, this article is going to formulate the key concepts in field cultural production which are assumed relevant to explain the dynamics of contemporary Indonesian literature.Keywords: paradigm, literature, sociology, trajector y, habitus, literar y field, strategy